Pentecostalism: A democratizing, liberating force for black women? - McDonald, Patrice (Journal of Pentecostal and charismatic Christianity, 2022)
Historically Pentecostals have used Galatians 3:26–28 to validate the equality between believers, regardless of a person’s sex. The scripture that states there is neither ‘male and female for you are all one in Christ Jesus’, seemingly promises a new community of people functioning equally and in unity. But if this is so, why have black women who historically occupied prominent places within Pentecostal revivals like Azusa Street had their influenced curtailed by denominations that evolved from the movement? And why do Pentecostal denominations like the Church of God (COG) and the British branch the New Testament Church of God (NTCG) deny women the highest rank of office as Bishops? This paper examines the impact of the black woman Lucy Farrow and suggests her prominence within Azusa created a precedent for black women leaders. The paper will contrast the policies of COG and NTCG with Farrow’s ministerial freedom and offer reflections on the position of black British Pentecostal women and consider whether Pentecostalism has been a liberating force.